FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN PRODUKSI GARAM DI PANTAI KUSAMBA KLUNGKUNG - Sumaryani, N. Putri; Parmithi, Ni Nyoman (Widyadari : Jurnal Pendidikan, 2019)
Salt is a complementary herb to make different types of cuisine to be delicious. Almost all types of food can not be separated from salt. Salt can be produced in a modern and traditional way in salt fields that lie on the lips of the beach. Gravy salt in Bali is indeed its existence began to decrease, because some areas are more developed as a tourist area. Growers of salt kusamba to this day still survive in developing the process of making salt bali.        Descriptive research conducted on salt farmers in Kusamba beach, Klungkung regency. Description is done based on data obtained from interviews of salt farmers in Kusamba Beach. The decrease of salt production at Kusamba beach of Klungkung Regency is caused by several factors such as long process of salt making and tradedional ways, community need for iodized salt, profession from salt farmer and natural condition factor.         The decline and the overturn of the profession of salt farmers is one of the problems that must be sought immediately solution because the loss of Balinese salt-making culture at Kusamba Beach certainly reduces the wealth of local culture owned by the island of Bali.